(untitled) (Brazilian Journal of Health Research, 2024)
Introduction: Thrombotic thrombocytopenic purpura (TTP) is a rare and severe disease characterized by the formation of abnormal blood clots that can lead to damage in various organs. It is marked by reduced ADAMTS13 activity levels and can be either acquired or congenital. Although conventional treatment with immunosuppressants and plasmapheresis is effective in most cases, a subgroup of patients develops refractory forms. The scarcity of therapeutic options for these patients, especially in resource-limited settings, makes managing refractory TTP challenging. We describe the case of an adolescent with acquired refractory TTP who achieved a complete response to treatment with bortezomib, focusing on age, diagnosis, therapy for refractory TTP, and its association with Systemic Lupus Erythematosus. Objective: To share this case with healthcare professionals in order to increase knowledge about refractory TTP and propose the inclusion of bortezomib as an alternative therapeutic option in selected cases. Methods: This is a descriptive observational study approved by the Medical Ethics Committee, with data obtained from the medical records of the Cassiano Antônio Moraes University Hospital (HUCAM). Results: Complete response after bortezomib therapy and the diagnosis of Systemic Lupus Erythematosus after 12 months of outpatient follow-up. Conclusion: In patients with acquired refractory TTP, the use of bortezomib shows efficacy and an appropriate safety profile, and should be considered in this scenario, as it is available in most specialized healthcare services.